On the train to brain gain in rural China - Yi Zhang; Anna Matz (University of Bonn, Center for Development Research (ZEF), 2017)
This study investigates the well-researched relationship between migration and the formation of human capital in the source region using a novel instrument: the existence of a local train station. We make use of Chinese panel data and of the fact that the decision to build a new train station is taken by the central government and unrelated to characteristics of a rural village receiving the station. As an intermediate result we find that train stations are negatively related to migration outflows, thus indicating that the facilitation of local employment through economic integration outweighs the reduction of migratory costs. Investigating variation within villages over time in the instrumental variables approach for the central research question, we see a positive effect of out-migration on educational attainment in the source region. Additional results suggest that the effect is stronger for male and young stayers.
Keywords: D10; I25; J61; 330; migration; human capital formation; instrumental variables; China; China